Implementation of Lean Six Sigma in Linen Management: A Case Study at Samarinda Medika Citra Hospital - Bahri, Syamsul; Rohendi, A.; Andikarya, Oke (Journal of Economics and Social Sciences (JESS), 2026)
Hospitals deliver healthcare services supported by both medical and non-medical ancillary units. The laundry unit functions as a non-medical support service that provides linen, particularly for inpatient care during cleaning procedures. Samarinda Medika Citra Hospital, a type C hospital with a capacity of 174 beds and a Bed Occupancy Rate (BOR) of 84% in 2024, faces several issues in linen management. These include linen loss, undocumented handovers between ward staff and laundry staff, discrepancies between the quantity of soiled linen collected and clean linen delivered, and the presence of worn-out linen with duplicate identifiers. This study aims to analyze the implementation of linen management using the Lean Six Sigma approach, identify existing challenges, and formulate improvement strategies based on Lean Six Sigma principles. This research employs a qualitative method with a descriptive case study design. The findings show that the application of Lean Six Sigma in linen management at Samarinda Medika Citra Hospital provides a foundation for enhancing efficiency and service quality through waste identification, workflow improvements, and strengthening of standard work procedures. Key challenges include staff understanding of efficiency principles and continuous improvement–based work standards, limitations in infrastructure, administrative systems, and management support. Improvement efforts include strengthening staff understanding and compliance with standard procedures through regular socialization and training, enhancing supporting facilities, developing digital recording systems, and promoting an adaptive, improvement-oriented work culture through coaching and performance-based incentives.